2022
DOI: 10.1177/10742484221107799
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Heart Failure With Reduced Ejection Fraction Associated With Electrocardiographic Outcomes Before and After Sacubitril/Valsartan

Abstract: Aim: Changes in QRS duration in patients with heart failure with reduced ejection fraction (HFrEF) after sacubitril/valsartan therapy is not fully understood. This study aimed to assess the association of duration of HFrEF diagnosis with electrocardiographic and echocardiographic outcomes between before and after sacubitril/valsartan. Methods: We included HFrEF patients who received naïve sacubitril/valsartan therapy for ≥3 months, between January 2016 and March 2018. All patients were divided into 2 groups ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Multiple studies have shown that using sacubitril‐valsartan can significantly decrease the N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP). This can further enhance left atrial function [ 21 ]. Sacubitril/valsartan is among the foundational therapies alongside a beta-blocker, MRA, and a sodium-glucose cotransporter-2 (SGLT2) inhibitor.…”
Section: Reviewmentioning
confidence: 99%
“…Multiple studies have shown that using sacubitril‐valsartan can significantly decrease the N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP). This can further enhance left atrial function [ 21 ]. Sacubitril/valsartan is among the foundational therapies alongside a beta-blocker, MRA, and a sodium-glucose cotransporter-2 (SGLT2) inhibitor.…”
Section: Reviewmentioning
confidence: 99%